Caring for pretty special children - Bryant-Shanklin, Mona (Columbia, S.C. : South Caroline ETV, 1989)
This is a six part video training series design to help professional care-givers work with'pretty special' children or abused children and their families
Keywords: Abused children -- Services for -- United States; Child abuse -- United States